2012
DOI: 10.1021/nl3024438
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered ClyA Nanopore Detects Folded Target Proteins by Selective External Association and Pore Entry

Abstract: Nanopores have been used in label-free single-molecule studies, including investigations of chemical reactions, nucleic acid analysis and applications in sensing. Biological nanopores generally perform better than artificial nanopores as sensors, but they have disadvantages including a fixed diameter. Here we introduce a biological nanopore ClyA that is wide enough to sample and distinguish large analytes proteins, which enter the pore lumen. Remarkably, human and bovine thrombins, despite 86% sequence identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
317
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 193 publications
(326 citation statements)
references
References 41 publications
6
317
1
2
Order By: Relevance
“…Since DHFR ST carries a weak negative charge (theoretical pI=6.7), these data indicate that the main driving force that promotes the entry of the protein into the cis vestibule of ClyA is the electroosmotic flow. 26,[38][39][40][41] Figure 2b). DHFR ST also rarely dwelled on a current level with lower residual current.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Since DHFR ST carries a weak negative charge (theoretical pI=6.7), these data indicate that the main driving force that promotes the entry of the protein into the cis vestibule of ClyA is the electroosmotic flow. 26,[38][39][40][41] Figure 2b). DHFR ST also rarely dwelled on a current level with lower residual current.…”
Section: Resultsmentioning
confidence: 98%
“…Recently we have shown that folded proteins might be trapped transiently inside the lumen of the Cytolysin A (ClyA) nanopore without the need of complex immobilization strategies or covalent chemistry. [25][26][27][28] Remarkably, ionic current recordings could monitor the binding of ligands to internalised proteins, indicating that an enzymatic activity can be translated into an electrical signal. 28 Conveniently, ClyA could be isolated in different oligomeric states, providing nanopores with identical chemical composition but different pore dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4À6 These nanopore experiments fall into three main categories: (i) experiments that detect protein transport and protein unfolding as domains are electrophoretically translocated through biological 7À11 or solid state 12À18 nanopores; (ii) experiments that interrogate proteinÀpore, 19À23 proteinÀ protein, 24À26 and proteinÀligand 27À29 interactions; and more recently (iii) experiments that detect native proteins by covalently attaching aptamers to the pore. 30,31 A relatively new addition to the first category are nanopore experiments that potentiate protein capture and unfolding by attaching a polyanion to the end of the protein strand which is captured in the electric field. 32À35 This technique has enabled the detection of unfolding intermediates 33,34 and post-translational modifications.…”
Section: November 17 2014mentioning
confidence: 99%
“…Die passende Selektivität für ein bestimmtes Biomolekül lässt sich über die Abmessungen der Nanopore festlegen. Dementsprechend wurden verschiedene biologische Membranproteine wie Areolysin, [2] Porin A aus Mycobacterium smegmatis (MspA), [3] ClyA, [4] FhuA, [5] membranadaptiertes phi29-Motorprotein [6] und SP1 [7] in nanoporenbasierten Analysesystemen eingesetzt. Eine andere Art von künstlichen Nanoporen sind Festkçrpernanoporen.…”
Section: Einführungunclassified